VR sickness analysis of long-term exposure to immersive Virtual Reality environments - Paulon, Matheus Montanha; Cheiran, Jean Felipe Patikowski; Araújo, Pedro Guilherme Da Silva; Amorim, Gabriel Souza Rodrigues De (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
Virtual Reality (VR) has advanced significantly in recent years, enabling highly immersive experiences across many domains. However, prolonged exposure to immersive VR environments can lead to VR sickness, which remains a barrier to widespread adoption. This exploratory study investigates how VR sickness symptoms evolve during long-duration immersive sessions using two different measures: the Simulator Sickness Questionnaire (SSQ) and the Fast Motion Sickness Scale (FMS). Seven participants were exposed to VR for up to three hours while their symptoms were periodically assessed. Visual patterns suggest three participant profiles (relentless, resilient, and withdrawers), while a Dynamic Time Warping (DTW) clustering reveals two distinct symptom progression patterns (susceptible and resistant). Furthermore, strong correlations were found between FMS and SSQ scores, and the SSQ disorientation subscale is a reasonable estimate of overall sickness for long-term sessions. These findings contribute to understanding the variability in VR sickness, highlighting the potential use of shorter assessment tools and clustering techniques to support research and design of immersive VR systems.